Endocrine Treatment and Targeted Therapy for Hormone Receptor–Positive, Human Epidermal Growth Factor Receptor 2–Negative Metastatic Breast Cancer: ASCO Guideline Update. Issue 35 (10th December 2021) - Burstein, Harold J.; Somerfield, Mark R.; Barton, Debra L.; Dorris, Ali; Fallowfield, Lesley J.; Jain, Dharamvir; Johnston, Stephen R. D.; Korde, Larissa A.; Litton, Jennifer K.; Macrae, Erin R.; Peterson, Lindsay L.; Vikas, Praveen; et al.
Abstract : PURPOSE: To update recommendations of the ASCO systemic therapy for hormone receptor (HR)-positive metastatic breast cancer (MBC) guideline. METHODS: An Expert Panel conducted a systematic review to identify new, potentially practice-changing data. RESULTS: Fifty-one articles met eligibility criteria and form the evidentiary basis for the recommendations. RECOMMENDATIONS: Alpelisib in combination with endocrine therapy (ET) should be offered to postmenopausal patients, and to male patients, with HR-positive, human epidermal growth factor receptor 2 (HER2)-negative, PIK3CA -mutated, ABC, or MBC following prior endocrine therapy with or without a cyclin-dependent kinase (CDK) 4/6 inhibitor. Clinicians should use next-generation sequencing in tumor tissue or cell-free DNA in plasma to detect PIK3CA mutations. If no mutation is found in cell-free DNA, testing in tumor tissue, if available, should be used as this will detect a small number of additional patients with PIK3CA mutations. There are insufficient data at present to recommend routine testing for ESR1 mutations to guide therapy for HR-positive, HER2-negative MBC. For BRCA1 or BRCA2 mutation carriers with metastatic HER2-negative breast cancer, olaparib or talazoparib should be offered in the 1st-line through 3rd-line setting. A nonsteroidal aromatase inhibitor (AI) and a CDK4/6 inhibitor should be offered to postmenopausal women with treatment-naïve HR-positive MBC. Fulvestrant and a CDK4/6 inhibitor should be offered to patients with progressive disease during treatment with AIs (or who develop a recurrence within 1 year of adjuvant AI therapy) with or without one line of prior chemotherapy for metastatic disease, or as first-line therapy. Treatment should be limited to those without prior exposure to CDK4/6 inhibitors in the metastatic setting. Additional information can be found at www.asco.org/breast-cancer-guidelines .